Protective Effect of Pumpkin Seed Extract on Bisphenol A Induced Testicular Toxicity in Adult Albino Rats (Medical Forum Monthly, 2023)
Objective: To determine the effects of Cucurbita Pepo (pumpkin) seeds extract on testicular toxicity induced by administration of Bisphenol A in adult male albino rats.Study Design: Experimental studyPlace and Duration of Study: This study was conducted at the Department of Anatomy, Postgraduate Medical Institute (PGMI), Lahore, Pakistan for a period of 28 days from 15 January 2020 to 11 February 2020.Materials and Methods: This experimental study comprised 30 male adult albino rats divided into three groups, A, B and C with 10 rats in each group. Group A was control and received distilled water for 28 days via oral gavage. Group B received Bisphenol at a dosage of 20mg/kg dissolved in 0.5mg of water for 28 days via oral gavage. Groups C received Bisphenol A plus Curcubita Pepo seeds extract. BPA was administered at a dosage of 20mg/kg body weight dissolved in 0.5ml distilled water and Cucurbita Pepo at a dosage of 300 mg/kg body weight dissolved in 2ml distilled water, once a day for 28 consecutive days through oral gavage method. Gross parameter included weight of both testis and Histological parameters like height of germinal epithelium and number of seminiferous tubules were analyzed.Results: The weight of paired testis of groups A, B and C was in range of 3.16-3.542g , 2.60-3.321.g and 3.0-3.43g respectively thus showing most weight reduction in group B. Height of germinal epithelium in groups A, B and C showed significant changes and was in range of 125-158 µm, 60-117µm and 92-151 µm respectively. The number of seminiferous tubules per field was nearly same as in group A and C but decreased in group B (p-value < 0.001).Conclusion: From the aforementioned results, it is clear about the adverse effects that BPA is inducing in human bodies and that pumpkin seeds have maintained testicular architecture ,reduced degeneration of germinal epithelium against BPA induced testicular damage.